The Effect of Work Motivation and Work Discipline on Employee Performance - Burhanudin Burhanudin; Deliah Fitriyani Pratiwi; Yayuk Apriyani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Employee performance can be used as a means to gain a competitive advantage if employee performance is superior to that of competing company employees. One of the companies experiencing problems with employee performance is the Wates Post office, which is located in the Wates sub-district, Kulon Progo district. There are indications that the performance of the Wates Post office employees is still not in line with the company's expectations. The low performance of these employees is partly influenced by work motivation and discipline. Based on these problems, the purpose of this study was to examine the effect of work motivation on employee performance and to examine the effect of work discipline on employee performance. The population in this study were 70 employees of the Wates Post office, Kulon Progo Regency, Yogyakarta Special Province. The data collection technique used a questionnaire, while the data analysis technique used multiple linear regression. The results showed that work motivation has a significant effect on employee performance and work discipline also has a significant effect on employee performance.